Do We Have the Right? How Polish Same-Sex Female Families Negotiate Turning Parenting Desires into Parenting Reality - Magdalena Wojciechowska (Przeglad Socjologii Jakosciowej, 2021)
This paper aims to shed light on how various micro- and macro-level contexts shape the parenting decision-making process among same-sex female couples. Drawing on my six-year study of two-mother planned families in Poland, I focus on voicing their experiences related to the process of family formation from its genesis and their related desires to fit in the social fabric despite being different. Specifically, I illustrate how those who navigate within the unfavorable socio-cultural climate give meanings to their experiences thereof, and thus negotiate their moral right to become mothers, as well as what kind of interactional and contextual factors shape how same-sex female couples in Poland embrace motherhood as an option they can choose. That is, how they decide to do what is largely considered normal—to enlarge their families.